PERFORMANCE EVALUATION OF FIELD AND GENETIC FOR SOME SIXTH RADIO GENERATION MUTANTS IN TOMATO - & et al., Alwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study was conducted at the fields of the Department of Horticulture and Landscape  Gardening, College of Agriculture, University of Baghdad " Abu Ghraib"  during the growing seasons 2013-2014  to Evaluate the Vegetative growth , yield  traits  and genetic parameter  of some tomato  mutants. Results showed significantly increased of plant height in M6-2 mutant 245cm in Comparison with M6-3 130 cm . M6-4 mutant significantly increasing of floral clusters 13 . Mutant M6-3 showed significantly increasing the average of, fruit weight 125.9g and plant yield 7.17 kg.plant-1 as comparison with M6-2 which showed decreasing of average of fruit weight and plant yield 79.40g and 4.38 kg.plant-1 respectively. Also results showed the highest Genetic variation components in plant height and average of fruit weight. The highest percentage of heritability in the broad sense plant height, floral clusters and average of fruit weight Analysis Hierarchical clustering showed that mutant was distributed in two groups the first group included mutants with M6-3 and  M6-4 , while the second group  included mutants  M6-2 and  M6-1.